2019
DOI: 10.1038/s41563-019-0468-3
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature stabilization of antiferromagnetic skyrmions in synthetic antiferromagnets

Abstract: Room-temperature skyrmions in ferromagnetic films and multilayers show promise for encoding information bits in new computing technologies. Despite recent progress, ferromagnetic order generates dipolar fields that prevent ultrasmall skyrmion sizes, and allows a transverse deflection of moving skyrmions that hinders their efficient manipulation. Antiferromagnetic skyrmions shall lift these limitations. Here we demonstrate that room-temperature antiferromagnetic skyrmions can be stabilized in synthetic antiferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
264
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(277 citation statements)
references
References 49 publications
10
264
2
1
Order By: Relevance
“…Other methods of introducing confining boundaries in the sample include using inhomogeneous pinning strength so that skyrmions in one region of the sample are more strongly (or less strongly) pinned than skyrmions in adjacent regions. It would be interesting to examine the effects of confinement on different types of skyrmions, such as antiferromagnetic skyrmions [75][76][77]. If the Magnus force is absent, the skyrmion dynamics would be con- sistent with what is found in an overdamped system and the edge transport would be absent.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods of introducing confining boundaries in the sample include using inhomogeneous pinning strength so that skyrmions in one region of the sample are more strongly (or less strongly) pinned than skyrmions in adjacent regions. It would be interesting to examine the effects of confinement on different types of skyrmions, such as antiferromagnetic skyrmions [75][76][77]. If the Magnus force is absent, the skyrmion dynamics would be con- sistent with what is found in an overdamped system and the edge transport would be absent.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31,32 ] Unfortunately, completely compensated magnetizations in ideal antiferromagnets result in challenges related to the detection and manipulation of antiferromagnetic skyrmions. [ 33–35 ] Fortunately, chiral behavior including interlayer Dzyaloshinskii–Moriya interactions (DMI) and stabilized skyrmions has been demonstrated in synthetic antiferromagnets (SAFs), [ 36–39 ] where the alignment of the magnetic moments can be tuned by manipulating two ferromagnetic layers coupled antiferromagnetically. [ 40,41 ] However, the microscopic origin of skyrmion generation is complicated, where opposite skyrmions in SAFs with two ferromagnetic layers have been theoretically proposed.…”
Section: Figurementioning
confidence: 99%
“…Thus, how to attain a stable nanoscale skyrmion under room temperature and a small applied field is a crucial task for device applications. Recently, Legrand et al [31] utilized magnetic force microscopy to image the skyrmions in the synthetic antiferromagnets at room temperature ( Fig. 3).…”
Section: Skyrmions and Topological Hall Effectmentioning
confidence: 99%
“…MFM observations of the BL-SAF system under external applied perpendicular field for μ0Hext = g 20 mT, h 60 mT and i 100 mT. [31] Unusual bulge and dent in the Hall resistance curves as a function of magnetic field are considered to be the features of the topological Hall effect, which stems from the scalar spin chirality in real space and is extensively utilized to detect the presence of chiral spin structure such as skyrmions. In 2009, Neubauer et al [21] reported that the topological Hall effect in the A phase of the transition metal compound MnSi, which testified the skyrmions structure with topological properties ( Fig.…”
Section: Skyrmions and Topological Hall Effectmentioning
confidence: 99%